Versican vs versikine: tolerance vs attack - Schmitt, Michael (Blood, 2016)
In this issue of Blood, Hope et al demonstrate the differential influence of versican and its proteolytic derivate, versikine, on the immune system. This discovery opens a new avenue for immunotherapies in multiple myeloma patients.